Tracing freshwater sources and particle discharge in Kongsfjorden: insights from a water isotope approach - Fang, Ling; Yang, Eun Jin; Yoo, Junho; Kim, Minkyoung (Frontiers in Marine Science, 2024)
Arctic fjords are inherently vulnerable to global warming, particularly because of the substantial freshwater influx resulting from the melting of glaciers. In this study, precipitation, river water, surface ice, and seawater samples from Kongsfjorden were collected to identify the main sources of freshwater. The dual water isotope (δ18O and δD) results and temperature–salinity profiles revealed that between 0% and 7% freshwater contributed to the fjord’s water. Furthermore, different freshwater sources for surface and deep water were identified by the dual water isotope analysis. Turbidity profiles confirmed the alter in particle discharge associated with surface runoff and subglacial discharge. Our study highlighted the sensitivity of water isotope analysis in elucidating the hydrological processes within the fjord system and demonstrated its potential for investigating the impact of meltwater on biological processes in the Arctic.